2002
DOI: 10.1364/ao.41.001780
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of biodeteriogens on stone cultural heritage by fluorescence lidar

Abstract: Biodeteriogens are an important cause of the weathering of a monument, particularly those made of stone, and their detection at an early stage of development helps to protect the monument from deterioration. Frequent mapping of biodeteriogen accumulation is therefore highly necessary. The use of fluorescence lidar for this purpose was introduced in 1995 and has been developed in subsequent years. Three main aspects emerged during this research: the possibility of discriminating between different biodeteriogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…LIF has been used by a number of groups to remotely image buildings using a point by point scan to detect bio-degradation on stones [95] and frescoes [88] and detecting past conservation interventions and identifying stone types [94].…”
Section: Towards Remote Spectral Imagingmentioning
confidence: 99%
“…LIF has been used by a number of groups to remotely image buildings using a point by point scan to detect bio-degradation on stones [95] and frescoes [88] and detecting past conservation interventions and identifying stone types [94].…”
Section: Towards Remote Spectral Imagingmentioning
confidence: 99%
“…Laser-induced fluorescence (LIF) is a powerful remote analysis tool that has been successfully applied to the real-time diagnosis of historical artworks, allowing the observation of features invisible to the naked eye, as pigment composition [1], biological attack [2] and trace of former restorations.…”
Section: Introductionmentioning
confidence: 99%
“…These advantages have encouraged its application in the real-time monitoring of historical frescoes, mosaics, paintings and stones. Former studies showed its high potential as a diagnostic tool for cultural heritage either operating in spectral [1,2] or time [5] resolved mode.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies were conducted in the laboratory for the characterization of protective treatments on stone samples 14 and for the investigation of the effects of biocide treatments 15 .…”
Section: Hyper-spectral Fluorescence Lidar Imaging Techniquementioning
confidence: 99%